Development of treeing detection method for cable with three insulation regions using tdr technique - Kuan T.M.; Mohd Ariffin A. (2023)
Treeing is a typical factor that contributes to aging of polymeric insulated cables. The occurrence and proliferation of these water trees cause electricity disruptions which interfere with the proper operation of the lines. This has resulted in a strong need for techniques to identify treeing degradation in polymeric insulated cables. In previous studies, a method that uses time domain reflectometry (TDR) technique to detect and locate water tree within two insulation regions has been shown to be feasible. Thus, this paper attempts to investigate on the potential of using the same method on cable with three insulation regions. Cable is modelled using MATLAB simulation tool to obtain the cable impedance for PSpice set-up simulation where the TDR technique is applied. The pulse reflections from the PSpice simulations are recorded and analysed to investigate whether this technique is capable of detecting water tree within three insulation regions. 2013 IEEE.